Surveillance of avian influenza viruses in Papua New Guinean poultry, June 2011 to April 2012 - Marinjho Jonduo; Sook-San Wong; Nime Kapo; Paskalis Ominipi; Mohammad Abdad; Peter Siba; Pamela McKenzie; Richard Webby; Paul Horwood (World Health Organization Regional Office for the Western Pacific, 2013)
We investigated the circulation of avian influenza viruses in poultry populations throughout Papua New Guinea to assess the risk to the poultry industry and human health. Oropharyngeal swabs, cloacal swabs and serum were collected from 537 poultry from 14 provinces of Papua New Guinea over an 11-month period (June 2011 through April 2012). Virological and serological investigations were undertaken to determine the prevalence of avian influenza viruses. Neither influenza A viruses nor antibodies were detected in any of the samples. This study demonstrated that avian influenza viruses were not circulating at detectable levels in poultry populations in Papua New Guinea during the sampling period. However, avian influenza remains a significant risk to Papua New Guinea due to the close proximity of countries having previously reported highly pathogenic avian influenza viruses and the low biosecurity precautions associated with the rearing of most poultry populations in the country.